Study of the Adsorption Thermodynamics and Kinetics of Lipoic Acid onto Three Types of Resin - Wei Ruixia; Chen Jinlong; Chen Lianlong; Fei Zheng-Hao; Li Ai-Min; Zhang Quanxing (Adsorption Science & Technology)
The adsorption of lipoic acid on three different types of resin was compared. Studies of the adsorption thermodynamics and kinetics of lipoic acid onto XAD-4, NDA-100 and ND-90 resins were carried out via static experiments. The results showed that the polar groups and micropore ranges associated with the resins played a significant role in the adsorption of lipoic acid. Such processes were exothermic and involved physical adsorption. The adsorption of lipoic acid onto XAD-4 resin corresponded to the formation of a Langmuir monolayer, with the adsorption velocity appearing to follow first-order kinetics. The adsorption data of lipoic acid onto NDA-100 and ND-90 resins were also well fitted by the Langmuir isotherm, which was associated with capillary condensation and volume filling of micropores besides monolayer adsorption. In contrast, the adsorption of lipoic acid onto NDA-100 and ND-90 resins involved two pore ranges: macropore + mesopore and micropore. The adsorption velocities for the two ranges followed first-order kinetics.